Investigation of the transient coupling between the dynamic laser beam absorptance and the melt pool - vapor depression morphology in laser powder bed fusion process. (February 2023) - Aggarwal, Akash; Shin, Yung C.; Kumar, Arvind
Highlights: High-fidelity ray-tracing model to study multiple reflections induced beam trapping. Investigation of coupling between optical and thermo-hydrodynamical phenomena. Absorption dynamics in powder bed and vapor depression for different melting modes. Results reveal highly non-linear fluctuating behavior of absorption for keyhole mode. Validation with in-situ X-ray imaging and in-house performed single-track experiments. Abstract: A predictive powder-bed model has been developed using open-source environments to investigate the coupling between the optical and the thermo-hydrodynamical phenomena for the laser powder bed fusion process. Firstly, discrete element modeling has been carried out to predict the configuration of powder particles over a substrate. Then, thermo-fluidic simulations for both the stationary and the moving laser irradiation have been carried out to investigate the melt pool dynamics, the vaporization induced keyhole depression instabilities, and the multiple reflections of the laser beam in the powder bed and the keyhole. The local absorptance and the reflectance of the laser beam at the static curvature of the solid powder particles and the dynamic interface of the vaporization-induced keyhole depression have been incorporated using a parallelized ray-tracing algorithm. The influences of laser power, scanning speed, beam spot diameter, and powder layer thickness on the melting mode and the transient beam absorption have been investigated. During the initial phase of melting in the powder bed, it was found that the laser absorption is very high (up to 73%) due to multiple reflections induced beam trapping. The absorption behavior for the conduction mode of melting was found to be dependent on the scanning speed of the laser beam. For the keyhole mode of melting, the temporal variation of the laser beam absorption shows a highly non-linear fluctuating behavior that is directly related to the vapor depression morphology of the melt pool. The numerically predicted attributes such as the initial laser beam absorptance, the transient melt pool-vapor depression morphology for the stationary laser irradiation, and the melt pool dimensions for the single-track deposition matches well with the findings of the published powder calorimetric measurement, published high-speed transmission X-ray imaging and the measured single-track deposited using the in-house laser powder bed fusion setup, respectively. Graphical abstract: Image, graphical abstract